The Kaizen Blitz accelerating breakthroughs in productivity and performance - Laraia, Anthony C. 1947- (National Association of Manufacturers series, 1999)
The Association for Manufacturing Excellence has pioneered a powerful version of kaizen - a process for achieving continuous improvement in an organization - called the Kaizen Blitz. This book will show you how to use this tool to deliver breakthrough improvements in your company in areas like productivity, inventory reduction, capacity expansion, and much more. You'll learn how to assemble a kaizen team that will determine solutions to your company's specific problems by designing new systems, correcting mistakes quickly and moving on, running and refining procedures, and ultimately demonstrating a new process in place in just a few days. You'll also read about top U.S. manufacturers who have successfully used the Kaizen Blitz to bring about radical, positive change.